Influence of stationary and bioreactor cultivation on Lentinula edodes (Berk) pegler lignocellulolitic activity - Regina, Magali [UNESP]; Broetto, Fernando [UNESP]; Giovannozzi-Sermanni, Giovanni; Marabotini, Rosita; Peranni, Claudio (Inst Tecnologia Parana, 2008)
This work aimed to study the stationary and periodically mixed culture of L. edodes to the production of lignocellulolitic enzymes activity. LE 95/17, LE 96/22 and Leax strains were incubated in 25 g of eucalyptus sawdust substrate in Erlenmeyer flasks in stationary culture at 25 degrees C and in a bioreactor with four complete rotations daily at 25 degrees C and 3% CO2. The samples were collected at 8, 11, 14, 17 and 20 days after the incubation. Oxidative and hydrolytic enzymes analyses were performed. Lignin peroxidase enzyme was not found in the lignolytic systernfor LE 95/17, LE 96/22 and Leax strains in the different incubation methods. The use of bioreactor could be a practicable system to induce the laccase activity for L22 and Leax and MnP activity for L17 and L22. The activity of the hydrolytic enzymes was higher in the stationary system in comparison to periodically mixed system in the bioreactor.

Lentinula edodes pertence ao grupo de fungos causadores da podridão branca, conhecidos pela capacidade efetiva de degradar compostos lignocelulósicos. No cultivo deste fungo o método de incubação, substratos e características genéticas determinam o comportamento enzimático. Este trabalho teve como objetivo verificar a influência do cultivo estacionário e em bioreator na atividade de enzimas lignocelulolíticas do L. edodes. As linhagens LE 95/17, LE 96/22 e Leax foram cultivadas em 25 g de substrato composto de serragem de eucalipto em frascos de Erlenmeyer, em cultura estacionária, sob de temperatura controlada a 25° C e em bioreator com quatro rotações diárias e completas, a 25° C e 3% de CO2. Foram coletados dados aos 8, 11, 14, 17 e 20 dias depois da incubação para atividade de enzimas oxidativas e hidrolíticas. A enzima lignina peroxidase não foi encontrada em nenhum dos tratamentos. O uso de bioreator pode ser visto como um sistema praticável para induzir atividade de laccase para L22 e Leax e atividade de MnP para L17 e L22. A atividade de enzimas hidrolíticas foi maior no sistema estacionário em comparação com o sistema misturado periodicamente em bioreator.
Keywords: shiitake; enzymes; agricultural residues